2016
DOI: 10.3390/c2010002
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Doped Hexagonal Boron Nitride: Analysis as π-Conjugate Molecules Embedded in Two Dimensional Insulator

Abstract: We analyzed the electronic structures of carbon-doped hexagonal boron nitride, focusing on the comparison with the corresponding π-conjugate hydrocarbon molecules and odd-number substitution by first principle calculation. The band gaps are about the half that of the HOMO-LUMO gaps of corresponding hydrocarbons, except for the cis-butadiene structure in which aromatic hexagonal ring formation is important. Odd number doping makes metallic materials with very different work functions, depending upon the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
4
5
0
Order By: Relevance
“…This would suggest possible way for tuning the band gap in CBN systems. Similar non-linear absolute decrease of the band gap was previously observed in several experimental [28,53] and theoretical studies [27,28,32,56], however, the band gap bowing observed in the bulk h-BN [53] is much smaller than the value reported in this paper. In other studies, the decrease of energy gap in C x (BN) 1−x alloy with C concentration is very abrupt in full analogy to our findings.…”
Section: Ordering and Density Of States In Cbn Stoichiometric Alloyssupporting
confidence: 91%
“…This would suggest possible way for tuning the band gap in CBN systems. Similar non-linear absolute decrease of the band gap was previously observed in several experimental [28,53] and theoretical studies [27,28,32,56], however, the band gap bowing observed in the bulk h-BN [53] is much smaller than the value reported in this paper. In other studies, the decrease of energy gap in C x (BN) 1−x alloy with C concentration is very abrupt in full analogy to our findings.…”
Section: Ordering and Density Of States In Cbn Stoichiometric Alloyssupporting
confidence: 91%
“…The lowest‐energy electronic transition of 1 appears in the near‐UV (375 nm) at significantly higher energy with respect to that of 2 (446 nm). In line with theoretical predictions,, this finding suggests that the B 3 N 3 ‐doping widens the molecular optical band gap (Δ Ε opt =0.53 eV). Furthermore, the absorption bands of 1 show noticeable vibrational substructures evidencing a high degree of rigidity of the molecular skeleton …”
Section: Figuresupporting
confidence: 87%
“…To shed further light on the structure‐property relation, we calculated the HOMO and LUMO orbitals for 1 and 2 (Figure ; Supporting Information, Figure S35). As observed by others,, it transpires that both orbitals are homogenously distributed on the π‐surface of 2 , whereas the LUMO for 1 is only located on the hexaphenylene rim. This suggests that the one‐electron reduction of 1 is likely to be confined on the hexaphenylene periphery excluding the B 3 N 3 ring, whereas that of 2 is localized on the entire carbon π‐surface.…”
Section: Figuresupporting
confidence: 69%
“…Recent theoretical works have revealed some of the interesting electronic structures of h-CBNs: [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] single-carbon dopant in h-BN forms midgap trap states, dopants tend to aggregate, and substantial band dispersion is expected with multiple-carbon doping. These are encouraging findings for the development of new types of semiconductors that are lightweight and composed of naturally abundant elements.…”
Section: Introductionmentioning
confidence: 99%